2013
DOI: 10.1603/ec12191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acute Toxicity of Essential Oil Of Garlic (<I>Allium sativum</I>) and Its Selected Major Constituent Compounds Against Overwintering <I>Cacopsylla chinensis</I> (Hemiptera: Psyllidae)

Abstract: In our screening program for insecticidal activity of the essential oils/extracts derived from some Chinese medicinal herbs and spices, garlic (Allium sativum L.) essential oil was found to possess strong insecticidal activity against overwintering adults of Cacopsylla chinensis Yang et Li (Hemiptera: Psyllidae). The commercial essential oil of A. sativum was analyzed by gas chromatography-mass spectrometry. Sixteen compounds, accounting for 97.44% of the total oil, were identified, and the main components of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 43 publications
4
40
1
Order By: Relevance
“…Ibrahim and Garba (2011) found garlic powder to be effective in the control of maize weevil. Zhao et al (2013) observed that the essential oil of A. sativum possessed contact toxicity against overwintering Cacopsylla chinensis (Hemiptera:Psyllidae) with an LC 50 value of 1.42 µg per adult. The two main constituent compounds diallyl trisulfide and diallyl disulfide, exhibited strong acute toxicity against the overwintering C. Chinensis with LC 50 values of 0.64 and 11.04 µg per adult respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ibrahim and Garba (2011) found garlic powder to be effective in the control of maize weevil. Zhao et al (2013) observed that the essential oil of A. sativum possessed contact toxicity against overwintering Cacopsylla chinensis (Hemiptera:Psyllidae) with an LC 50 value of 1.42 µg per adult. The two main constituent compounds diallyl trisulfide and diallyl disulfide, exhibited strong acute toxicity against the overwintering C. Chinensis with LC 50 values of 0.64 and 11.04 µg per adult respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few studies focused on the analysis of these two compounds have been reported in the scientific literature: for CAD (Blakemore and Thompson 1983; Tsai and Chen 1984;Gursale et al 2010;Ma et al 2011;Zhao et al 2014) and for DAD (Germain et al 2002;Hsieh et al 2012;Casella et al 2013;Zhao et al 2013). Due to their volatility, GC was the preferred instrumental separation technique.…”
Section: Analytical Methods Development and Optimizationmentioning
confidence: 99%
“…Amonkar and Banerji (1971) identified DAD as one of the major components in garlic oil having antagonistic properties against pests of economic importance such as potato tuber moth, red cotton bug, red palm weevil, houseflies, and mosquitoes (Kimbaris et al 2009;Mostafa et al 2013;Zhao et al 2013;Wang et al 2014a). Its SDS states that when pure, it is a combustible liquid, toxic if swallowed, and a skin, eye, and respiratory irritant.…”
Section: Introductionmentioning
confidence: 99%
“…Mukerji (1953) has reported that oral administration of garlic to children is dangerous and could even be fatal though it has antibacterial effect due to the active principle allicin (Cavallito and Bailey, 1944). According to Zhao et al (2013), the two main constituent compounds, diallyl trisulfide and diallyl disulfide, exhibited strong acute toxicity against the overwintering C. chinensis, with LC 50 values of 0.64 and 11.04 µ g per adult, respectively. The larvicidal effect and principle of Allium sativa has also been extensively conducted and isolated (Amonkar and Banerji, 1971).…”
Section: Introductionmentioning
confidence: 99%